Ausência/presença de artigo definido diante de antropônimo na cidade mineira de Ponte Nova: um estudo sociolinguístico - Glauciane da Conceição dos Santos (2012)
This work presents an analysis of the absence/presence of definite articles before proper nouns, the anthroponyms, in the light of the theoretical and methodologicalassumptions of Labovian Sociolinguistics (1972). The analysis considers the speech of residents of Ponte Nova city, which is 190 km from the capital of the state of Minas Gerais, Belo Horizonte. During the conduction of this research, it was observed that the realization of the definite article before an anthroponym occurs in variant forms in consonance with linguistic and extra-linguistic factors. The corpus of this research was composed of 933 occurrences, obtained from interviews conducted with 16 informants, 8 male and 8 female, divided into two age groups, consisting of the young group, from 18 to 25, and of the adultgroup, over 60. A quantitative analysis using the statistical program Goldvarb/Varbrul (2001) was performed to analyse the corpus. The results obtained show that only the factora preposition before an anthroponym is relevant amongst the linguistic factors. The relevant extra-linguistic factors, in turn, are age groups and public persons.